Exploring the Influence of Financial Literacy, Financial Attitudes, Self-Control, and Hedonistic Lifestyle on Generation Z's Financial Management Behavior: A Study on PayLater Usage in Jakarta - Vincent Colin; Tannia Tannia; Elkunny Dovir Siratan; Caliska Aldira Kusbiantoro (Asian Journal of Management Analytics, 2026)
This study investigates the influence of financial literacy, financial attitude, self-control, and lifestyle on financial management behavior in the context of PayLater usage among Generation Z in Jakarta. The research aims to determine whether these factors significantly affect to shaping responsible financial behaviors, particularly concerning online payment services. A quantitative approach was used and data were processed using IBM SPSS version 22, utilizing primary data gathered through an online questionnaire distributed to university students and young workers aged 17-26 who have used PayLater services. The results reveal that financial literacy, financial attitude, and self-control significantly impact financial management behavior, while lifestyle, specifically hedonistic tendencies, does not show a significant influence. These findings underscore the importance of improving financial literacy and self-control to enhance financial decision-making within Generation Z.